Evaluation of indoxacarb and fipronil (s)-methoprene topical spot-on formulations to control flea populations in naturally infested dogs and cats in private residences in Tampa FL. USA - Dryden, Michael W.; Payne, Patricia A.; Smith, Victorene E.; Chwala, Monica; Jones, Emery; Davenport, Jacob; Fadl, Gabrielle; Martinez-Perez de Zeiders, Maria F.; Heaney, Kathleen; Ford, Pamela; Sun, Fangshi (My University, 2013)
Background: A study was conducted to evaluate and compare the effectiveness of two different spot-on topical flea products to control flea infestations on naturally infested dogs and cats in Tampa, FL USA. Methods: Thirty-two dogs and 3 cats with natural flea infestations living in 18 homes were treated topically with a 19.53% w/w spot-on formulation of indoxacarb. Another thirty dogs and 2 cats living in 19 different homes were treated topically with either fipronil (9.8% w/w)/(s)-methoprene (8.89% w/w) or fipronil (9.8% w/w)/(s)-methoprene (11.8% w/w), respectively. All products were applied according to label directions by study investigators on day 0 and again between days 28 and 30. Flea populations on pets were assessed using visual area counts and premise flea infestations were assessed using intermittent-light flea traps on days 0, 7, 14, 21, 28–30, 40–45, and 54–60. Results: A single application of the indoxacarb or fipronil (s)-methoprene formulations reduced flea populations on pets by 97.8% and 85.5%, respectively within 7 days. One month (28–30 days) after treatment the indoxacarb and fipronil (s)-methoprene formulations reduced on-animal flea burdens by 95.0% and 49.5%, respectively. Following two monthly applications of either the indoxacarb or fipronil (s)-methoprene formulations, pet flea burdens were reduced by 99.1% and 54.8%, respectively, by days 54 – 60. At the end of the two month study, 77.1% and 15.6% of the dogs and cats in the indoxacarb and fipronil (s)-methoprene treatment groups, respectively were flea free. Flea numbers in the indoor-premises were markedly reduced in both treatment groups by days 54–60, with 97.7% and 84.6% reductions in intermittent-light flea trap counts in the indoxacarb and fipronil (s)-methoprene treatment groups, respectively. Conclusions: This in-home investigation conducted during the summer of 2013 in subtropical Tampa, FL, is the first published U.S field investigation of the indoxacarb topical formulation. The indoxacarb formulation was able to effectively control flea populations in heavily flea infested pets and homes. The efficacy achieved by the fipronil (s)-methoprene formulation against flea infestations on these pets was lower than in previous investigations using the same study design.
Keywords: Ctenocephalides felis felis; Cats; Dogs; Fipronil; Flea control; Indoxacarb